REPRESENTASI BULLYING DALAM FILM "CRY ME A SAD RIVER": Studi Analisis Semiotika - Cahaya Wahyudi (2024)
The incidence of bullying in the educational environment in Indonesia has seen an increase, as revealed in data released by the Indonesian Child Protection Commission (KPAI) and through news reports. In this context, film plays a crucial role as a medium for conveying messages to the public on a universal scale, including messages related to bullying. Therefore, this research aims to represent instances of bullying and unveil the meanings contained within the film "Cry Me Sad a River" through Roland Barthes' semiotic analysis. The research methodology used by the researcher is qualitative, utilizing the semiotic analysis approach of Roland Barthes. This approach is employed to decipher denotative, connotative, and mythic signs in detail. The research data is divided into primary data derived from the film "Cry Me Sad a River," encompassing narratives and images depicting bullying actions, and secondary data obtained from literature supporting the research. The units of analysis in this study include elements in the film related to the portrayal of bullying, with a specific focus on 12 selected scenes. The research findings indicate signs affirming acts of bullying, including indications of physical violence, verbal abuse, cyberbullying, and relational bullying. Motivational factors driving bullying actions are also identified, such as harboring resentment accumulated from being a bullying victim. Other contributing factors include a lack of awareness in educational institutions regarding bullying incidents, family discord causing difficulties for children to discuss bullying problems, and a lack of empathy from bullying perpetrators resulting in denial of the bullying scenes they engage in.